PENGELOLAAN TATA RIAS PENGANTIN BLITAR KARTIKA RUKMI TERHADAP KEWIRAUSAHAAN BERBASIS KEARIFAN LOKAL PESERTA DIDIK DI LEMBAGA KURSUS DAN PELATIHAN ELLY DUA PUTRI BLITAR - Agustiani, Elma (J+PLUS UNESA, 2021)
This study aims to obtain local wisdom values contained in Javanese bridal make-up taught at the Elly Dua Putri Blitar course and training institute. Through exploratory studies with a qualitative approach and phenomenological design, data were collected through observation and interviews. The data were analyzed by using the data display cycle, data reduction, verification and conclusion drawing. The research found local perfume values: (1) luwing cinandi bun, (2) kawung wulan purnama wedding dress, and (3) make-up or beautiful makeup which is full of meaning. These local wisdom values are integrated in the learning process at the Elly Dua Putri Blitar course and training institute with a learning model called the MaHaKeTang technique, namely the process of coaching, student involvement, and network building strategies